Is It Possible for Children in Duchenne Muscular Dystrophy to Preserve Cardiac Function with Medical Assistance? - Han Geul Kim; Lucy Youngmin Eun; Han Ki Park (MDPI AG, 2020)
In patients with Duchenne muscular dystrophy (DMD), death secondary to cardiac or respiratory failure typically occurs in the second or third decade without treatment. Although cardiac dysfunction is treated with standard heart-failure strategies, it remains insufficient in DMD children. The purpose of this study was to evaluate the efficiency of cardiac medication and noninvasive ventilator support in DMD cardiomyopathy children with analyzing echocardiographic data. Forty-eight DMD children patients were included and divided into 2 groups by left ventricular (LV) ejection fraction (EF) at the time of initial treatment. Group 1: LV EF ≥ 45% and Group 2: LV EF < 45%. p-values were calculated using a Linear mixed model to estimate the association between cardiac medications and echocardiographic measurements. Before and after cardiac medications, the change values were significantly different in interventricular septal thickness at end diastole (IVSd), interventricular septal thickness at end systole (IVSs), left ventricular internal diameter end systole (LVIDs), left ventricular posterior wall thickness end diastole (LVPWd), ejection fraction (EF), fractional shortening (FS), deceleration time (DT), DT slope, Lat A' and Lat E/E' (p < 0.05). Group 2 patients revealed to take more kinds of cardiac medications than Group 1 (p < 0.05) including ACEIs, beta-blocker, and inotropics, then LV EF was better preserved in Group 2 than Group 1. It is certainly helpful to take individualized medical combination therapy including inotropic agents for cardiomyopathy in DMD children patients with EF < 45%.